Design of a Biped Climbing Robot: Simulation, Comparison and Implementation - Huang, Tao; Cao, Rundong; Wu, Xinliang (Manufacturing Technology Journal, 2023)
In this paper, the design of a robot is proposed to replace manual labor in completing tasks on vertical planes. The aim is to enhance automation in the workplace and eliminate direct human involvement to ensure personal safety. Firstly, the robot's structure is designed as a five-joint biped with vacuum adsorption capabilities. The forward and inverse kinematics of the robot are analyzed. Secondly, using simulation by ADAMS, five key performance metrics are quantitatively analyzed for both this robot and a Hexapod robot. These metrics include adsorption reliability, external load-bearing capacity, friction coefficient adaptability, obstacle-crossing capacity, and joint torque. Thirdly, the main control chip used for this robot is STM32F407. The circuit system design and physical implementation of the robot are based on this chip. Finally, experiments are conducted to study the actual performance of the robot in vertical cleaning tasks.
Keywords: Wall-climbing robot; bped robot; vertical cleaning